Hibridisasi Simulated Annealing dengan Algorithm Evolutionary dalam Penyelesaian Travelling Salesman problem (TSP) - Erdiwansyah Erdiwansyah; Taufiq A. Gani; Yuwaldi Away (Jurnal Komputer, Informasi Teknologi, dan Elektro, 2016)
The process of traveling salesman from one city to the others is a form of costs optimization, time consuming so the process can minimize the cost and time of travel. Travelling Salesman Problem (TSP) is an optimization problem to determine the shortest distance in a travel route in each city can which only be passed exactly once in one trip and then return to the city where sales was begin their journey. In this study, hybridization of simulated annealing with evolution algorithm was proposed to minimize the individual convegency in a population of each generation before reaching optimum point. This research proposes algorithm Hybridization SA with the SA and AE AE itself, namely the computational time and optimization of results. Keywords- Algorithm Evolutinary, Simulated Annealing, Hybrid SA and AE.